Highly efficient method of utilizing waste silica hazards - Singh, Anup Kumar; Sudhakar, Vediappan (Process Safety and Environmental Protection, 2021)
Silica gels are the significant commodity solid waste produced by organic laboratories and pharmaceutic industries. Although use of silica gels is continuously growing, the proper methods of re-utilizing silica waste are yet limited. Hence, it demands a non-traditional approach to transform these silica waste into some other useful products apart from using them as a well-known road construction materials. Hereby, we report the fabrication and applications of monolithic polymer-silica composites by ice-templating technique from laboratory waste silica-gels, using green approach. To the best of our knowledge, the fabrication of organic-inorganic hybrid sponges from the particles of hundreds of microns is not reported to date. Scaffolds S-60, S-120, S-180, and S-300, were prepared from laboratory discarded silica gels. The morphological, physicochemical, flame-retardant, and liquid absorbent properties of these self-standing scaffolds were analyzed. Results showed that the incorporation of silica particles in the scaffolds turned them into a flame-retardant sponge. These properties make the sponges ideal for making non-flammable cushions, applicable in automobiles, aircrafts, chemical laboratories, hospitals, and other areas of applications. Due to the large porous structures, these scaffolds possess excellent absorption properties and may absorb almost every kind of liquid ranging from oils to acids. Therefore, these scaffolds are also a remarkable absorber for oils and hazardous liquids spillage, such as acids, and can be used as foam for chemical packing applications. (C) 2021 Institution of Chemical Engineers. Published by Elsevier B.V. All rights reserved.
Keywords: Acid absorber; Flame-retardant; Ice-templating; Laboratory silica waste; scaffolds